Estimation of water production cost in the feasibility analysis of RO systems - Atikol, U; Aybar, HS (Elsevier, 2005)
In this study a practical method is developed where the recent experiences are modified according to the local conditions for making reasonable estimations of the unit production cost of fresh water for new RO systems to be constructed. Some of the most important cost components are determined as the capital cost, the electricity cost, and the costs related to maintenance, membrane replacement and chemicals. In the construction of a 1000m(3)/day RO plant in Eastern Mediterranean University, it was possible to take the sea water through a well on the coast before feeding it into the RO plant. It was also planned to use an energy recovery system which would reduce the overall production cost of fresh water. Although a similar plant was discovered to have produced fresh water at a cost of 0.86 $/m(3), after making a comparison of all the main factors affecting the unit cost of water it was estimated that the unit cost of water should be approximately 0.68 $/m(3) for the new plant to be constructed in the university. It was observed that the unit cost is approximately 0.7$/m(3) after the plant was erected and put into operation.
European Conference on Desalination and the Environment -- MAY 22-26, 2005 -- St Margherita Ligure, ITALY
Keywords: reverse osmosis; water production cost